في بعض المعايير الدموية لذكور واناث الفئران المختبرية Neotigason تاثير عقار - سعيد, سلمى (University of Thi-Qar Journal of Science, 2010)
Neotigason (Acitretin) is a retinoid for the oral treatment of severe cases of psoriasis and disorders of keratinization. Consequently this study has been designed to investigate the physiological affects of Neotigason on the lab male and female Musmusculus L., these animals divided to following groups (n=12), thirty six: 1. First group I.P. injected with normal saline.2. Second group I.P. injected with 10 mg/day of Neotigason. 3. Third group I.P. injected with 20 mg/day of Neotigason. Mice were tested 15 days after the onset of the first injection and following physiological parameter were recorded:-A. Number of White Blood Cells (W.B.C.).B. Measure of Packed Cells Volume (P.C.V.).C. Concentration of Haemoglobin (Hb).The result of the current study showed that there is a significant decrease (P≤ 0.01) in packed cells volume (P.C.V.) and concentration of haemoglobin (HB). To both doses sexes. It is also noticed that a significant decrease (P≤ 0.01)in the number of white blood cells (W.B.C.) in the dose 10 mg/day and a significant increase in the number of white blood cells in the dose 20 mg/day in female mice and no significant decrease in he number of white blood cells in the dose 20 mg/Kg/day and significant increase (P≤ 0.01) in the number of white blood cells in the dose 10 mg/Kg/day for the male mice.